Oxide-cladding aluminum nitride photonic crystal slab: Design and investigation of material dispersion and fabrication induced disorder - Melo, E. G.; Carvalho, D. O. [UNESP]; Ferlauto, A. S.; Alvarado, M. A.; Carreño, M. N.P.; Alayo, M. I. (AIP Publishing, 2016)
Photonic crystal slabs with a lower-index material surrounding the core layer are an attractive choice to circumvent the drawbacks in the fabrication of membranes suspended in air. In this work we propose a photonic crystal (PhC) slab structure composed of a triangular pattern of air holes in a multilayer thin film of aluminum nitride embedded in silicon dioxide layers designed for operating around 450 nm wavelengths. We show the design of an ideal structure and analyze the effects of material dispersion based on a first-order correction perturbation theory approach using dielectric functions obtained by experimental measurements of the thin film materials. Numerical methods were used to investigate the effects of fabrication induced disorder of typical nanofabrication processes on the bandgap size and spectral response of the proposed device. Deviation in holes radii and positions were introduced in the proposed PhC slab model with a Gaussian distribution profile. Impacts of slope in holes sidewalls that might result from the dry etching of AlN were also evaluated. The results show that for operation at the midgap frequency, slope in holes sidewalls is more critical than displacements in holes sizes and positions.